Traffic Congestion in Kabul City and Suggestion for Sustainable Development - Yusufzada, Shaheen; Xia, Zhiqiang; Poyan, Sayed Mustafa; Sediqi, Maryam; Wahdat, Mohammad Naim; Wafayar, Zalmai; Sukhandan, Mohammad Nasim (American Journal of Social Sciences and Humanities, 2020)
Traffic congestion is a global problem all over the world but very harmful for developing countries like Afghanistan. This study intends to explore the relation between traffic congestion and urban dwellers selection behavior on current location for living, and also examine the causes and effects which exist behind traffic congestion. A case study approach has been adapted and Kabul city is taken as a case since it is capital city and has big regional connection with other areas. To obtain comprehensive picture about the cause and effects of Kabul traffic congestion, the study also depend on various published documents and primary data has been collected through the semi-structure questionnaire and group discussion. This study reveals that there are branches of reason such as shortage of necessarily urban infrastructure, improper human behavior, poor traffic management and demo-graphically populations’ problems which are causing traffic congestion in Kabul. Many issues such as social, environmental, economic and air pollution are resulted by the traffic congestion. This study recommends that government need to take steps for strengthening the construction of transportation infrastructure, implementing the traffic law, increasing the number of public buses, decentralizing the government agencies and commercial center, improving traffic management system and applying electronic system for traffic management for reducing traffic congestion and ensuring comfortable city life. This study will help researcher, government policy planner and decision makers to improve the appropriate road safety measures for passengers.